Periodische und statistische Beziehungen zwischen den jährlichen Häufigkeiten der Großwetterlagen Europas und der räumlichen Verteilung der jährlichen Niederschlagssummen in Teilen Westafrikas - Klaus, Dieter (ERDKUNDE, 1975)
Between 1967 and 1973 substantial increases in the frequency of meridional circulation types in the summer months were observed. There could have led to a decline in precipitation in the subtropics which was as statistically significant for some parts of West Africa as the occurrence of above-average annual precipitation totals in the Sahel area when mixed circulation forms predominate over Europe. The frequency distributions of annual precipitation totals in West Africa show spatial patterns which can be explained over a long period in terms of alternation between the monsoon and harmattan regimes. The deviations of the frequency distributions from a normally distributed structure show changes which are dependent on geographical longitude. The time series of major circulation types in Europe and the time series of a number of West African stations were studied by spectral analysis. This showed the working of the ’Southern Oscillation’ of the sunspot cycle and a 18-23 year period. Cross-correlation and coherences analyses indicated a 30 year period, also apparently indicated by the historically-attested occurrence of droughts in the Sahel.